PENGARUH PENGGUNAAN MEDIA ANIMASI AUDIO VISUAL TERHADAP KETERAMPILAN MENYIMAK CERITA ANAK PESERTA DIDIK KELAS V DI UPT SPFSD NEGERI MANGASA - Mutmainna, Nurul; Amrah; Abdullah, Muhammad Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study focuses on the effect of using audiovisual animation media on fifth-grade students' listening skills in stories at the SPF Unit (Technical Instructional Facility) of Mangasa Public Elementary School in Makassar City. The background of this study stems from the importance of listening as a basic language skill, which remains a challenge for many students due to low narrative recall and lack of concentration during the learning process. This study used a quantitative approach with a quasi-experimental design involving two groups of students. One group was taught using audiovisual animation media, while the other group used conventional learning methods. Data were obtained through a listening skills test in the form of essay questions, then analyzed using statistical tests to determine differences in results between the two groups. The results showed that the use of audiovisual animation media resulted in significant differences in students' listening skills after the treatment. Animation media helped students understand the story content more clearly and maintain concentration during the learning process. Overall, this study concludes that audiovisual animation media is an effective alternative in listening instruction, particularly in creating a more engaging and accessible learning experience for elementary school students. These findings provide practical implications for teachers in selecting relevant learning media and can serve as a reference in developing strategies for delivering material in elementary schools.